Horizontal Axis Wind Turbine Efficiency Optimization Through Tip Radius Modification on 4:5 Flat Taper Blades - Sahid, Sahid; Anandia, Faranita Putri; Wattimena, Christopher Johanes Edsel; Pratiwi, Okta Ayu; Tantri, Riris Annisa Tarra; Barid, Muhammad (Politeknik Negeri Semarang, 2025)
This study aims to investigate how changing the roundness of the back edge of blades affects a 4:5 flat taper wind turbine. Tests used blades with 5 mm, 10 mm, and 15 mm rounded edges, compared to a 5 mm notched blade, across wind speeds from 3 to 9 m/s. The results show the 5 mm rounded edge works best at low wind speeds, with an efficiency of 11.12% at 3 m/s. At higher wind velocities, the 15 mm rounded blade demonstrated superior aerodynamic performance, attaining an efficiency of 1.63% at 7 m/s. The rounded trailing edge improved aerodynamic behavior by minimizing turbulence and enhancing flow stability. Therefore, the optimal edge radius should be determined based on regional wind characteristics, especially for low-speed wind zones typical of Indonesia